Phylogenomic analysis provides insights into MADS-box and TCP gene diversification and floral development of the Asteraceae, supported by de novo genome and transcriptome sequences from dandelion (Taraxacum officinale) - Xiong, Wei; Risse, Judith; Berke, Lidija; Zhao, Tao; van de Geest, Henri; Oplaat, Carla; Busscher, Marco; Ferreira de Carvalho, Julie; van der Meer, Ingrid M.; Verhoeven, Koen J. F.; Schranz, M. Eric; Vijverberg, Kitty (Frontiers in Plant Science, 2023)
The Asteraceae is the largest angiosperm family with more than 25,000 species. Individual studies have shown that MADS-box and TCP transcription factors are regulators of the development and symmetry of flowers, contributing to their iconic flower-head (capitulum) and floret. However, a systematic study of MADS-box and TCP genes across the Asteraceae is lacking. We performed a comparative analysis of genome sequences of 33 angiosperm species including our de novo assembly of diploid sexual dandelion (Taraxacum officinale) and 11 other Asteraceae to investigate the lineage-specific evolution of MADS-box and TCP genes in the Asteraceae. We compared the phylogenomic results of MADS-box and TCP genes with their expression in T. officinale floral tissues at different developmental stages to demonstrate the regulation of genes with Asteraceae-specific attributes. Here we show that MADS-box MIKCc and TCP-CYCLOIDEA (CYC) genes have expanded in the Asteraceae. The phylogenomic analysis identified AGAMOUS-like (AG-like: SEEDSTICK [STK]-like), SEPALATA-like (SEP3-like), and TCP-PROLIFERATING CELL FACTOR (PCF)-like copies with lineage-specific genomic contexts in the Asteraceae, Cichorioideae or dandelion. Different expression patterns of some of these gene copies suggest functional divergence. We also confirm the presence and revisit the evolutionary history of previously named “Asteraceae Specific MADS-box genes (AS-MADS).” Specifically, we identify non-Asteraceae homologs, indicating a more ancient origin of this gene clade. Syntenic relationships support that AS-MADS is paralogous to FLOWERING LOCUS C (FLC) as demonstrated by the shared ancient duplication of FLC and SEP3